Microwave Filter and Antenna for Wireless Communication Systems - Zakaria, Zahriladha; Sam, Weng Yik; Abd Aziz, Mohamad Zoinol Abidin; Meor said, Maizatul Alice (2012)
This paper presents the investigation and characterization of integrated microwave filter and antenna to reduce the overall physical volume for RF/ microwave front-end subsystems. This study focuses on the integrating of rectangular Substrate Integrated Waveguide (SIW) filter with rectangular microstrip patch antenna to produce filtering and radiating element in a single device. To proof the concept, the integrated microwave filter and antenna at center frequency of 2 GHz is demonstrated and validated through simulation and analysis. This class of microwave filters and antenna integration would be useful in microwave systems where the reduction of size and weight as well as cost is very important such as in base stations and multiplexer in any communication systems.